The Diameter of a Zero-Divisor Graph for Finite Direct Product of Commutative Rings - Atani, S. Ebrahimi; Kohan, M. Shajari (Sarajevo Journal of Mathematics, 2024)
This paper establishes a set of theorems that describe the diameter of a zero-divisor graph for a finite direct product $R_{1}× R_{2}×…× R_{n}$ with respect to the diameters of the zero-divisor graphs of $R_{1},R_{2},…,R_{n-1}$ and $R_{n}(n>2).$ 2000 Mathematics Subject Classification. 05C75, 13A15